The electrophysiological time course of somatosensory spatial remapping: vision of the hands modulates effects of posture on somatosensory evoked potentials. Issue 6 (8th July 2013) - Rigato, Silvia; Bremner, Andrew J.; Mason, Luke; Pickering, Alan; Davis, Rob; van Velzen, José
Abstract: We investigated the electrophysiological correlates of somatosensory processing under different arm postures by recording event‐related potentials at frontal, central and centroparietal sites during tactile stimulation of the hands. Short series of 200 ms vibrotactile stimuli were presented to the palms of the participants' hands, one hand at a time, in either uncrossed‐ or crossed‐hands postures. The manipulation of posture allowed us to investigate the electrophysiological processes underlying the spatial remapping of somatosensory stimuli from anatomical into external frames of reference. To examine somatosensory spatial remapping independently of its effects on attentional processes, the stimuli were presented unpredictably in terms of location, and in temporal onset. We also examined how vision of the limbs affects the process of remapping. When participants had sight of their hands (Experiment 1) the effect of posture was observed over regions contralateral to the stimulated hand from 128 ms, whereas when their limbs were covered (Experiment 2) effects of posture influenced the ipsilateral regions from 150 ms. These findings add to an increasing body of evidence which indicates that sight of the hand modulates the way in which information in other modalities is processed. We argue that in this case, sight of the hand biases spatial encoding of touch towards an anatomical frame of reference. Abstract : We investigated the electrophysiological correlates of somatosensory processing under different arm postures by recording event‐related potentials at frontal, central, and centroparietal sites during tactile stimulation of the hands. Short series of 200 ms vibrotactile stimuli were presented to the palms of the participants' hands, one hand at a time, in either uncrossed‐ or crossed‐hands postures.